Understanding the Puzzling Risk-Return Relationship for Housing - Han, Lu (Review of Financial Studies, 2013)
[Standard theory predicts a positive relationship between risk and return, yet recent data show that housing returns vary positively with risk in some markets but negatively in others. This paper rationalizes these cross-market differences in the risk-return relationship for housing, and in so doing, explains the puzzling negative relationship. The paper shows that when the current house provides a hedge against the risk associated with the future housing consumption, households are willing to accept a lower return to compensate for risk, thus weakening the positive risk-return relationship. Further, in markets with less elastic housing supply and a growing population, hedging incentives can be sufficiently strong to make the relationship negative. The empirical analysis confirms these predictions, suggesting that hedging incentives, housing supply, and urban growth are indeed central to understanding the risk-return relationship for housing.]